Singapore Airlines : staying ahead in a changing industry landscape. - Tay, Ivan Ming Hoe. (2012)
This case highlights some of the key issues facing SIA in the challenging aviation industry today. Readers can expect an in-depth discussion on the factors affecting SIA, analyse how SIA should prioritise and deal with the issues and propose a feasible recommendation.